Factors Influencing the Stability of Blood Eosinophils Counts in Chronic Obstructive Pulmonary Disease Patients - Cheng-Sen Cai; Jun Wang (Canadian Respiratory Journal)
Blood eosinophil (EOS) has recently been recognized as a biomarker for chronic obstructive pulmonary disease (COPD) patients. However, few studies have concentrated on the stability of blood eosinophil counts (BEC), and those studies have produced varying results. With further research, we have found minor drawbacks and vulnerabilities that lead to the variability of the results. This paper enumerates several areas of relevant research with varying conclusions to further investigate the stability of BEC in COPD patients.